Cycloferon Efficacy in the Treatment of Acute Respiratory Tract Viral Infection and Influenza During the Morbidity Outbreak in 2009-2010 - M. G. Pomantsov; S. V. Golofeevsky (Антибиотики и Химиотерапия)
Clinical signs of acute respiratory tract viral infection and influenza in 150 patients under the standard symptomatic therapy with cycloferon, an early interferon 1 and 2 inductor are described. The patients were randomized by the body temperature on the day of the medical advise seeking. The clinical process of the respiratory tract infection was characterized by the second increase of the body temperature stated in 31.8% of the patients. By the clinical signs the infection was mixed (virus-virus) that explained the second increase of the body temperature. Normalization of the temperature was stated on the 4th or 5th day of the observation. The catarrhal and intoxication syndromes were observed for no more than 5 days. When the treatment was started in time (on the day of the medical advise seeking), cycloferon provided minimization of the intoxication and catarrhal syndromes and normalization of the body temperature on the 4th day of the therapy without the use of antibacterial agents.